HADIS SHAHIH, HADIS HASAN, HADIS DHOIF DAN HADIS MAUDHU’I - Diyah Pratiwi,; Fadhila Rahmi; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the classification of ḥadīth authenticity ṣaḥīḥ, ḥasan, ḍaʿīf, and mawḍūʿ (fabricated) as a fundamental framework for determining the evidentiary authority of prophetic reports in Islamic scholarship. The study is motivated by the persistent circulation and use of ḥadīths without adequate verification in academic discussions, religious instruction, and digital platforms, which may lead to inaccurate religious conclusions. The aims of this research are to: (1) explain the definitions and criteria of each ḥadīth category based on the principles of muṣṭalaḥ al-ḥadīth; (2) identify major factors contributing to ḥadīth weakness and the emergence of fabricated reports; and (3) map the implications of each category’s authority (ḥujjiyyah) for legal reasoning and the reinforcement of Islamic values. This research employs a library based (literature) method with descriptive analytical and comparative approaches by reviewing primary classical works of ḥadīth methodology along with relevant supporting studies. The findings indicate that ṣaḥīḥ ḥadīths fulfill the requirements of uninterrupted chains of transmission, transmitter integrity and precision, and freedom from irregularity (shudhūdh) and hidden defects (ʿillah). Ḥasan ḥadīths meet similar criteria but with a lower level of transmitter precision compared to ṣaḥīḥ. Ḍaʿīf ḥadīths result from the failure to satisfy one or more acceptance conditions in either the chain (isnād) or the text (matn). Mawḍūʿ reports are fabricated and therefore cannot be used as evidence; disseminating them without clarifying their status is religiously impermissible. The study recommends strengthening ḥadīth verification literacy through consistent application of isnād and matn criticism and the use of authoritative references to ensure responsible and accurate utilization of ḥadīth in education, preaching, and research.